José Zorrilla, the Last Epic Bard of Spanish Literature (Castilla. Estudios de Literatura, 2019)
In 1889, José Zorrilla was crowned as National Poet in “la Alhambra”. This fact meant the clímax of the multiple recognitions he had received all along his life. Besides, that title bolsted up the image of Zorrilla as national bard that he had always pursued, and finally got thanks to his work: Granada, poema oriental. Precedido de la leyenda de Al-Hamar (1852). The following paper attempts to study the conception and constitution of this piece, Zorrilla’s vastest one, which emerged inside the Romantic fashion of Orientalism and became the last epic poem of Spanish literature.
Keywords: Zorrilla; Granada; epic poetry; national poet; Orientalism